The Influence of Career Development, Work Ethic, Communication on Job Satisfaction of Employees of the West Nusa Tenggara Provincial Trade Office - Maulidya Aisya Ibrani Junior; Djoko Suprayetno; Sulaimiah Sulaimiah (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to determine the effect of career development, work ethic, and communication on job satisfaction of employees of the Trade Office of West Nusa Tenggara Province. The type of research used is causal associative research with a quantitative approach. The population in this study were all employees of the West Nusa Tenggara Province Trade Office. The number of samples used in this study were 61 people using the saturated sampling method. Data collection techniques used were interviews, documentation and distributing questionnaires containing questions about career development, work ethic, and communication on job satisfaction. The analysis tool used is Multiple Linear Regression Analysis using the SPSS 25 for Windows program. The results of data analysis show that; (1) career development has a positive and significant effect on job satisfaction (2) work ethic has a positive and significant effect on job satisfaction, (3) communication has a positive and significant effect on job satisfaction.